The Value of Serum Midkine Level in Diagnosis of Hepatocellular Carcinoma - Karim Y. A. Shaheen; Abeer I. Abdel-Mageed; Eslam Safwat; Ashraf M. AlBreedy (International Journal of Hepatology)
Background and Aim. Identification of sensitive biomarkers to improve early diagnosis of HCC is needed. We aimed to evaluate serum midkine (MDK) as a biomarker for HCC diagnosis. Patients and Methods. 40 HCCs, 30 liver cirrhosis patients, and 30 healthy subjects were enrolled. Serum MDK using ELISA was measured in all included subjects. Results. Serum MDK was significantly elevated in HCC group compared to cirrhotic and healthy control groups (0.625 versus 0.15 and 0.125 ng/mL), respectively. No significant association was found between MDK and either BCLC stage, tumor diameter, tumor number, or AFP level. Receiver operating characteristic curve showed that best cutoff for MDK and AFP was 0.387 and 88.5 ng/mL, respectively. Area under the curve of MDK was significantly larger than that of AFP (0.941 versus 0.671). The sensitivity of MDK at 0.387 ng/mL for HCC diagnosis was significantly higher than that of AFP at cutoffs 20, 88.5, and 200 ng/mL (92.5 versus 62.5, 40, and 25%), respectively. Sensitivity of MDK reached 93.3% in patients with AFP <20 ng/mL. Moreover, MDK at 0.387 ng/mL had significant better sensitivity than AFP at 20 ng/mL in distinguishing HCC from BCLC 0/A (90 versus 40%). Conclusion. Serum MDK might be a potential diagnostic marker for HCC particularity in its early stages.